Zika Virus Requires the Expression of Claudin-7 for Optimal Replication in Human Endothelial Cells - Zoladek, Jim; Legros, Vincent; Jeannin, Patricia; Chazal, Maxime; Pardigon, Nathalie; Ceccaldi, Pierre-Emmanuel; Gessain, Antoine; Jouvenet, Nolwenn; Afonso, Philippe V. (Frontiers in Microbiology, 2021)
Zika virus (ZIKV) infection has been associated with a series of neurological pathologies. In patients with ZIKV-induced neurological disorders, the virus is detectable in the central nervous system. Thus, ZIKV is capable of neuroinvasion, presumably through infection of the endothelial cells that constitute the blood-brain barrier (BBB). We demonstrate that susceptibility of BBB endothelial cells to ZIKV infection is modulated by the expression of tight-junction protein claudin-7 (CLDN7). Downregulation of CLDN7 reduced viral RNA yield, viral protein production, and release of infectious viral particles in several endothelial cell types, but not in epithelial cells, indicating that CLDN7 implication in viral infection is cell-type specific. The pro-viral activity of CLDN7 in endothelial cells is ZIKV-specific since related flaviviruses were not affected by CLDN7 downregulation. Together, our data suggest that CLDN7 facilitates ZIKV infection in endothelial cells at a post-internalization stage and prior to RNA production. Our work contributes to a better understanding of the mechanisms exploited by ZIKV to efficiently infect and replicate in endothelial cells and thus of its ability to cross the BBB.